2017
DOI: 10.1016/j.jsxm.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Collagenase Clostridium histolyticum in the Treatment of Acute-Phase Peyronie’s Disease

Abstract: Background Peyronie’s disease (PD), defined as the abnormal formation of fibrous plaque(s) in the tunica albuginea of the penis, is a chronic condition that afflicts 3% to 13% of the US male population; there is no current research on the efficacy and safety of collagenase Clostridium histolyticum (CCH) in the treatment of acute phase PD. Aim To examine the efficacy and safety of CCH in the treatment of acute-phase PD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 4 publications
4
29
1
Order By: Relevance
“…In the present cohort, 39% of patients received CCH at an early phase of PD (<12 months) and we showed that duration of the disease may influence treatment success. In contrast to the findings of the present study, Nguyen et al [25] demonstrated no statistical difference in CCH treatment efficacy between those in the acute phase of the disease and those in the stable phase. These discrepancies may be explained by the rigid definition of stable disease, which was based on the PD duration in that study, while we considered PD duration as a continuous variable, expressed in months, to be more accurate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present cohort, 39% of patients received CCH at an early phase of PD (<12 months) and we showed that duration of the disease may influence treatment success. In contrast to the findings of the present study, Nguyen et al [25] demonstrated no statistical difference in CCH treatment efficacy between those in the acute phase of the disease and those in the stable phase. These discrepancies may be explained by the rigid definition of stable disease, which was based on the PD duration in that study, while we considered PD duration as a continuous variable, expressed in months, to be more accurate.…”
Section: Discussioncontrasting
confidence: 99%
“…The angle of curvature was assessed, using a goniometer protractor, during erection after an intracavernous injection of prostaglandin E1. The IIEF-15 questionnaire considered the severity of erectile dysfunction, classified as follows: severe (score ≤10); moderate (scores 11-16); and mild (scores [17][18][19][20][21][22][23][24][25]. IIEF-15 sub-scores were also assessed, including IIEF-erectile function (IIEF-EF), IIEF-orgasmic function, IIEF-sexual desire, IIEF-intercourse satisfaction and IIEF-overall satisfaction.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although surgery remains the gold standard treatment option for patients with stable PD, it is not recommended for men in the active phase. On the other hand, collagenase clostridium histolyticum (CCH) represents the only licensed drug for the minimally invasive treatment of PD [14,15], however the acute phase of PD is not currently an indication for CCH therapy [3,16,17]. Four studies [18][19][20][21] demonstrated significant improvements in penile curvature after 10 or 15 mg intralesional verapamil, although the protocols varied widely, ranging from 6 to 12 injections.…”
Section: Discussionmentioning
confidence: 99%
“…Small case series suggest that collagenase clostridium histolyticum is also effective in patients with acute phase disease [11,14]. While in one of these series, patients in the acute and chronic phases of Peyronie’s achieved a similar improvement in curvature (approximately 15°), the other patients in the acute phase benefited more (20° versus 13.9°).…”
Section: Intralesional Therapymentioning
confidence: 99%